2021
DOI: 10.3389/fnins.2021.665258
|View full text |Cite
|
Sign up to set email alerts
|

Influence of High Pass Filter Settings on Motor Evoked Potentials

Abstract: ObjectiveMotor evoked potentials (MEP), obtained by transcranial magnetic stimulation (TMS) are a common tool in clinical research and diagnostic. Nevertheless, reports regarding the influence of filter settings on MEP are sparse. Here, we compared MEP amplitudes and signal to noise ratio (SNR) using multiple high pass filter (HPF) and notch filter settings.Materials and MethodsTwenty healthy subjects were enrolled in the study. Recruitment curves were obtained with HPF settings varied at 10, 20, 50, and 100 H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…The derivative-based method provided very small errors across the full spectrum of signal-to-noise ratios (SNRs) computed as the ratio between the MEP peak-to-peak amplitude and the maximum noise in the baseline as suggested by [21]. In particular, the largest errors occurred at very low SNR and never at high values, in a comparable fashion to human raters (see additional file 3).…”
Section: Algorithms' Performancementioning
confidence: 79%
See 1 more Smart Citation
“…The derivative-based method provided very small errors across the full spectrum of signal-to-noise ratios (SNRs) computed as the ratio between the MEP peak-to-peak amplitude and the maximum noise in the baseline as suggested by [21]. In particular, the largest errors occurred at very low SNR and never at high values, in a comparable fashion to human raters (see additional file 3).…”
Section: Algorithms' Performancementioning
confidence: 79%
“…The latter risks to be present especially when latency is used to make comparisons: as a diagnostic measure to differentiate healthy from pathological; or in a research setting to study stimulation paradigms effects (e.g. to evaluate the effect of different current directions of TMS on excitability of the corticospinal tract [21]). Given the high accuracy in the healthy dataset, this new tool opens possibilities to answering further research questions related to cortico-spinal tract conduction times and brainnetwork science.…”
Section: Discussionmentioning
confidence: 99%
“…A very recently published study [35] investigated the problem of filtering MEPs with a view to reducing the signal-to-noise ratio. Here, too, it could be shown that the filters with the lowest cutoff frequency (10 Hz and 20 Hz in this case) showed the lowest amplitude distortion and, moreover, they were able to show that better signal-to-noise ratio could be achieved for these filter parameters as well.…”
Section: Discussionmentioning
confidence: 99%
“…RMT is defined as the minimum stimulation intensity that motor-evoked potential (MEP) is significant in at least half of the trials. A trial is considered a success when MEP has minimal value of 50 μV (usually 50–100 μV) [ 25 , 26 ]. Thanks to neuronavigation, it was easy to find a hotspot and achieve a high MEP for all participants in almost all trials.…”
Section: Methodsmentioning
confidence: 99%